Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report, 2018)
This Technical Assistance Report discusses the recommendations made by the IMF mission to assist the Central Bank of Bosnia Herzegovina (CBBH) in the compilation and dissemination of government finance statistics (GFS) in accordance with the guidelines of the Government Finance Statistics Manual 2001 and its update. It is recommended that the legal basis for the collection of GFS data by the CBBH should be strengthened to get more easily access to (confidential) data which serve as input for GFS. The production of GFS could benefit from more cooperation between the CBBH, the Ministries of Finance, and the National Bureau of Statistic. A permanent working group of compilers of macroeconomic statistics in different institutions should be set up to this aim.